Upaya Pengendalian Terhadap Kualitas Air Bersih Akibat Aktivitas Penambangan Di Kelurahan Manongkoki Kabupaten Takalar - Israyanti Israyanti; Rudi Latief; Emil Salim Rasyidi; Muhammad Idris Taking (Journal of Urban Planning Studies, 2021)
The purpose of this study was to determine the magnitude of the impact of clean water quality due to mining activities in Manongkoki Village and to determine efforts to control clean water quality due to mining activities in Manongkoki Village, Takalar Regency. This research is a field research with the method of collecting data through surveys and documentation, with a quantitative approach method. The analysis used in this research is to use simple mathematical calculations with the equation pH = -log [H3O+] and descriptive analysis. The results showed that the impact of clean water quality at the research site was due to mining activities where the depth of the mine excavation was deeper than the depth of the well, causing a lack of clean water quality and as an effort to control the quality of clean water by using the filtration method using biofiltration technology and technology membrane to filter water from an alkaline pH to neutral again.